Disappeared to Ethiopia’s Bermuda: Tales by a Puppet - Van De Rede, Lauren (Kronos: Southern African Histories, 2020)
At the Red Terror Martyrs’ Memorial Museum (RTMMM) in Addis Ababa, Ethiopia, there sits upon a wall a chart of the torture houses used during a campaign of terror waged by the Derg regime that ruled Ethiopia from 1974 to 1987. Among the most notable was Bermuda House – named as such because, ‘if someone went in there, they would not come back out’.1 Alongside the wall chart is a puppet, bound up in strings and rods, that is staged and used to depict the wofe lala torture technique (also known as Technique No. 8 and falanga)2 used by the military junta. In this article, I attempt to think through the roles played by the puppet, and by spaces such as Bermuda House, as contributory interlocutors to the grand narrative of the Red Terror as constructed by the museum. In doing so, I consider ways in which the puppet, through its staging and performance, stands proxy for the still missing who disappeared during the Red Terror. I also show how the puppet illustrates an entanglement between genres of missingness while acting on its audiences as its object. The puppet, I argue, as a proxy for the still-missing missed, stages the tension that exists between atrocities that are named as terror in popular discourse but recognised as genocide under Ethiopian law. Furthermore, the puppet stages not only the bleeding of these tensions into one another but also the question of what remains unacknowledged between them.